An Electro-Thermal Analysis of a Variable-Speed Doubly-Fed Induction Generator in a Wind Turbine - Yingning Qiu; Wenxiu Zhang; Mengnan Cao; Yanhui Feng; David Infield (Energies, 2015)
This paper focuses on the electro-thermal analysis of a doubly-fed induction generator (DFIG) in a wind turbine (WT) with gear transmission configuration. The study of the thermal mechanism plays an important role in the development of cost-effective fault diagnostic techniques, design for reliability and premature failure prevention. Starting from an analysis of the DFIG system control and its power losses mechanism, a model that synthesizes the thermal mechanism of the DFIG and a WT system principle is developed to study the thermodynamics of generator stator winding. The transient-state and steady-state temperature characteristics of stator winding under constant and step-cycle patterns of wind speed are studied to show an intrinsic thermal process within a variable-speed WT generator. Thermal behaviors of two failure modes, i.e., generator ventilation system failure and generator stator winding under electric voltage unbalance, are examined in details and validated by both simulation and data analysis. The effective approach presented in this paper for generator fault diagnosis using the acquired SCADA data shows the importance of simulation models in providing guidance for post-data analysis and interpretation. WT generator winding lifetime is finally estimated based on a thermal ageing model to investigate the impacts of wind speed and failure mode.